2022
DOI: 10.1093/advances/nmab099
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Dietary Na:K Ratio—Considerations for Design of an Intervention Study to Impact Blood Pressure

Abstract: Despite medical, dietary, and lifestyle recommendations and drug advancements, hypertension persists as among the most prevalent noncommunicable diseases in the US population, and control remains elusive. Uncontrolled hypertension may increase the risk of serious illness from various other health challenges, including cardiovascular and renal responses. Adoption of a healthy diet is a consistent core element of lifestyle modifications that are recommended for mitigation of hypertension. The dietary sodium-to-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These findings suggested that a urinary Na/K ratio reduction over the long term might promote a reduction in BP among older adults. Therefore, future studies are required to further examine the association between a Na/K ratio reduction and a BP reduction in later life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that a urinary Na/K ratio reduction over the long term might promote a reduction in BP among older adults. Therefore, future studies are required to further examine the association between a Na/K ratio reduction and a BP reduction in later life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, our study focused on the effect of a high-K + diet on blood pressure by evaluating renal Na + transporters along the nephron without measuring blood pressure itself. Second, the ratio of Na + to K + , rather than the Na + /K + intake, is reportedly necessary for volume and blood pressure homeostasis [32]. As shown recently, the urinary Na + /K + ratio was found to exhibit a significantly stronger relationship with blood pressure compared with BP than Na + or K + alone [33].…”
Section: Discussionmentioning
confidence: 90%
“…Ma et al (2022) showed that higher sodium and lower potassium intakes were associated with a higher cardiovascular risk. Therefore, increasing potassium intake and reducing sodium intake is required, with a call for attention to the diet's Na:K ratio (Baer et al, 2022). The RDAs of sodium and potassium were 1,000-1,500 mg/day and 2,000-3,400 mg/day, respectively (National Academies of Sciences Engineering and Medicine, 2019).…”
Section: Discussionmentioning
confidence: 99%